Antioxidant Activity of Extract Combination from Moringa oleifera Leaves and Garcinia mangostana L. Pericarp - Hartanti, Yesiska Kristina; Lukas, Diksa T.; Hardy, Junius (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Radical-related diseases can be mitigated through natural antioxidant therapies that help regulate the formation and accumulation of free radicals. The pericarp of Garcinia mangostana L. and the leaves of Moringa oleifera are well-known for their antioxidant properties due to their high level of bioactive compounds, such as flavonoids, phenolics, and xanthones. This study aimed to explore the antioxidant capabilities of these two herbal extract combinations. Using the maceration method with 96% ethanol, the extraction yields were 11.4% w/w for M. oleifera and 24.11% w/w for G. mangostana. Qualitative phytochemical screening revealed differences in secondary metabolites, particularly steroids and triterpenes, between the two extracts. The antioxidant activity was categorized based on EC50 values, with crude G. mangostana showing very strong activity (<50 µg/mL) and M. oleifera classified as strong (50–100 µg/mL). Combinations of the extracts (2–10 ppm) produced very strong antioxidant activity but showed reduced efficacy compared to G. mangostana alone, suggesting antagonistic interactions based on combination index (IC) calculation. This study emphasizes the need for multiple antioxidant assays to evaluate diverse mechanisms and recommends further research to optimize synergistic effects in herbal extract combinations.